EP300 Modulates MCM8 Transcription and Augments the Malignant Phenotype of Hepatitis B Virus–Positive Hepatocellular Carcinoma Cells - Fang Xue; Tian‐Feng Sun (Kaohsiung Journal of Medical Sciences, 2025)
ABSTRACT Chronic infection with the hepatitis B virus (HBV) remains one of the primary drivers of the development of hepatocellular carcinoma (HCC), a highly aggressive malignancy with a grim prognosis. This study focused on the role of E1A‐binding protein p300 (EP300) in the malignant phenotype of HBV‐positive HCC cells and its functional mechanism. Increased EP300 expression was detected in HBV‐positive tumor tissues and cells compared to their control counterparts. Silencing EP300 reduced tumorigenic activity, proliferation, viability, migration, invasion, and resistance to apoptosis of HBV‐positive cells and reduced the concentrations of HBV infection markers HBsAg and HBeAg. These effects were achieved, at least in part, through downregulation of minichromosome maintenance 8 homologous recombination repair factor (MCM8). MCM8 was identified as a target of EP300 and mediated by acetylation modification. MCM8 was upregulated in HBV‐positive tumors and HCC cells while decreasing following EP300 silencing in cells. However, the restoration of MCM8 expression in these cells rescued their malignant properties. In summary, this study suggests a role for EP300‐mediated MCM8 upregulation in the malignant properties of HBV‐positive HCC.